The Implementation of Diversion and Restorative Justice in the Juvenile Criminal Justice System in Indonesia - Aji, Wikan Sinatrio (Faculty of Law, Universitas Negeri Semarang, 2019)
Children are a younger generation successor to the nation that must be protected. In some cases children can do a mischief that fall into the categories of offenses and called as children in conflict with the law. Children in conflict with the law is different in terms of handling the criminal offenses committed by adults. Currently with Law Number 11 of 2012 on the Criminal Justice System of Children (SPPA) which has sought diversion and restorative justice in terms of handling child conflict with the law. From the results of this study concluded that the policy formulation the concept of diversion and restorative justice pursuant tonLaw Number 11 of 2012 on the Criminal Justice System of Children (SPPA) and its implementation rules have been set regarding policy concept of diversion and restorative justice with the aim that children who commit acts the criminal is no longer confronted in the judicial process but through an alternative solution,namely the completion of which is the restoration to its original state (restorative justice) will but of formulating the policy is still not perfect because it found some weakness. While in the implementation of diversion and restorative justice in the the settlement of children in conflict with the law in Pati District Court already sought remedies which reflect restorative justice approach by implementing law enforcement diversion and restorative justice but there are still many obstacles occurred in the settlement of children in conflict with the law in Pati District Court.